A REALLY WHEEZY WAY TO SAVE MONEY. Issue 9 (17th August 2016) - Li, Grace; Almossawi, Ofran; Dulfeker, Hasna; Jones, Vicky; Taylor, Felicity
Abstract : Aim: To compare the palatability of oral non-soluble and oral soluble prednisolone tablets in paediatric patients admitted to the general paediatric wards in an acute London Trust. Method: As part of ongoing quality improvement initiatives, the Paediatric and Pharmacy departments compared tolerability of soluble versus non-soluble prednisolone in a group of 27 patients. Using a modified 5 point hedonic scale with 'smiley' faces we measured palatability and tolerance (swallowed versus refusal or vomiting) over two three week periods: the first period whilst soluble prednisolone was dispensed (n=17) and the second period after the switch to non-soluble prednisolone had been made (n=10). All data were collected by doctors and nurses on the two paediatrics wards. Results: We found acceptance of prednisolone to be similar before and after formulations were switched: 2 non-tolerated doses before (n=17) versus 3 non-tolerated doses after the switch (n=10). We found that 'disguising' the taste of the non-soluble prednisolone within a portion of sugar free jam, or mixed with 5 ml of sugar-free blackcurrant cordial, helped with acceptance, although both soluble and non-soluble formulations were frequently reported to be "Yuk"! Conclusions: The Trust has since made the switch to non-soluble prednisolone for all paediatric inpatients and for take home medications. An information leaflet has been developed for parents or carers to understand how to crush the prednisolone tablets. We have not had any parent or carer reported difficulty in preparing or administering the medication. Children under 15 account for 37.8% (20, 510 of 54, 300) of annual hospital admissions for acute asthma.1 A minimum course of 3 days' oral steroids are recommended in the BTS/SIGN 2014 guideline on the management of asthma.2 This acute Trust covers a population of over 300, 000 in deprived boroughs of London. A typical three-day course of soluble prednisolone (at 2 mg/kg as per guidance, or approximately 20 mg) costs £20.88, compared to £2.48 for the equivalent dose of non-soluble prednisolone dispensed with a tablet crusher. Several hospital trusts have switched to using non-soluble prednisolone in order to achieve cost savings, but there have been anecdotal reports of poor palatability, raising concerns about compliance with taking medication once discharged. The switch from a soluble to a non-soluble formulation of prednisolone represents an annual saving of more than £44, 000 for this hospital alone and, at scale, could realise substantial potential savings to the NHS, without compromising patients' clinical care.